Flexible, self-healing and portable supramolecular visualization smart sensors for monitoring and quantifying structural damage - Jiao, Dezhi; Gu, Sihan; Cheng, Li; Li, Shuoqi; Liu, Chengbao (Materials horizons, 2025)
Visually monitoring micro-crack initiation and corrosion failure evolution is crucial for early diagnosis of structural health and ensuring safe operation of infrastructures. However, existing damage detecting approaches are subject to the limited-detection of heterogeneous structures, intolerance of harsh environments, and challenge of quantitative analysis, impeding applications in structural health monitoring (SHM). Herein, we present a stretchable, semi-quantitative, instrument-free, supramolecular SHM sensor by integrating a polyurea elastomer with sensitive corrosion-probes, enabling localized corrosion monitoring and quantification of failure dynamics. Initially, a correlation between visual monitoring signals and structural health status is proposed, and sensor-based image processing software that accurately quantifies structural failure indicators (crack scale, corrosion reactivity and deterioration status) is proposed. Moreover, this sensor can be fabricated as multiple derivatives: a coating or patch covered on metallic substrates and an ionic-responsive test strip, ensuring real-time detection of the initiation of pitting, degradation events of metallic components and convenient monitoring of ion concentrations in corrosive media. Furthermore, the inherent geometric plasticity and dynamic hydrogen-bonded network validates the reliability for heterogeneous components and stability under extreme environments of sensors. This portable, smart SHM strategy established the channel-transformation model from corrosion dynamics to visual signals, exhibiting prospects for structural monitoring in offshore energy-harvesting equipment. A novel supramolecular damage sensor featuring unique ionic recognition, robust failure visualization and excellent environmental adaptability is constructed for monitoring and quantifying structural health.